(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The purpose of this research is to investigate the effects of individual entrepreneurialorientation (EO) and entrepreneurial intention (EI) on the link between entrepreneurial role models (ERM)and entrepreneurship education (EE). Data on 255 management and business university students whohave finished the entrepreneurial education programme is gathered using a survey approach. PLS-SEMis used to process the data in order to assess the research model. According to the study’s findings,students’ access to entrepreneurial role models and educational opportunities influences their ability tobe imaginative, proactive, and risk-takers—three traits that are essential to an individual’sentrepreneurial orientation. ERMs, however, don’t directly affect EI. The primary conclusion of this study,which shows that solely individual innovativeness affects entrepreneurial intention, is that EO has animpact on EI. Personal initiative and risk-taking, however, have been shown to have no effect onemotional intelligence. By analysing the impact of ERMs on each element that makes up an individualentrepreneurial orientation (IEO) and its EI, this study was able to close a research gap. Additionally, thisresearch model offers a thorough study model on how pre-entrepreneurial exposure affects IEO and howthat affects EI.